Prenatal Diagnosis of Congenital Syphilis Using Two- and Three-Dimensional Ultrasonography: Case Report. (21st August 2012) - Araujo Júnior, Edward; Martins Santana, Eduardo Felix; Rolo, Liliam Cristine; Nardozza, Luciano Marcondes Machado; Moron, Antonio Fernandes
Abstract : The numbers of syphilis cases have been increasing considerably, especially in eastern europe, thereby contributing towards greater chances of cases of congenital syphilis. Some of the complications of congenital syphilis can be detected on two-dimensional ultrasonography (2DUS), and these are generally manifested in the second trimester of pregnancy. The commonest ultrasonographic signs are hepatosplenomegaly, placentomegaly, and fetal growth restriction, while lower-frequency occurrences include intrahepatic calcifications, ascites, fetal hydrops, and even fetal death. Three-dimensional ultrasonography (3DUS) is a relatively new imaging technique that is adjuvant to 2DUS and enables detailed assessment of the fetal surface anatomy. We present a case of a 21-year-old primigravida with a diagnosis of congenital syphilis, with obstetric 2DUS findings of hepatosplenomegaly, ascites, pericardial effusion and hyperechogenicity of the cerebral parenchyma. 3DUS in rendering mode allowed clear assessment of the fetal limbs, especially the feet, which appeared twisted and lacked some toes. It allowed the parents to understand the pathological condition better and improved prenatal management and neonatal followup. 3DUS can be used routinely for assessing fetal malformations resulting from congenital infections.